Costing Methods as a Means to Measure the Costs of Pharmacogenomics Testing. (11th September 2020) - Siamoglou, Stavroula; Karamperis, Kariofyllis; Mitropoulou, Christina; Patrinos, George P
Abstract: Clinical implementation of pharmacogenomics and personalized medicine interventions relies on addressing important financial aspects of the delivery of genetic testing to the patients, be it from public or private providers. Details on how to determine the cost items of the genetic testing are often limited. The goal of this study is to present a costing methodology in order to estimate and measure the costs as far as the technical process of pharmacogenomics testing is concerned. Moreover, an overall cost mindset strategy based on the selective genotyping workflow to guide specialized laboratories of interest effectively is provided. We particularly accounted for the resources consumed within the laboratory premises such as cost of reagents for DNA isolation, cost of consumables, cost of personnel, while costs associated with patient recruitment, blood sample collection and maintenance, administration costs in the hospital, and costs of blood sample shipment were not taken into consideration. Our article presents the first-time detailed information on a costing framework for pharmacogenomic testing that could be employed to laboratories involved in routine clinical implementation of pharmacogenomics.